I hate to read. - Marshall, Rita.; Delessert, Etienne (Mankato, MN : Creative Editions, 1992)
As a third-grader who hates to read unwillingly looks at a book, the characters come alive and interest him so much that he really begins to care about them, and begins turning the pages...
Keywords: Books and reading -- Fiction; Characters in literature -- Fiction